Decolonial discourses in Chimamanda Ngozi Adichie’s Americanah: : transgressing cultural and linguistic borders - de Oliveira Lanari, Luiza (Cadernos CESPUC de Pesquisa Série Ensaios, 2025)
This article aims to, drawing on Decolonial Studies and Sociolinguistics, analyze how bilingual subjects are conceived in the novel Americanah, written in 2013 by the Nigerian author Chimamanda Ngozi Adichie. The decolonial concepts of territoriality presented by Ngũgĩ wa Thiong’o, as well as Walter Mignolo’s languaging/bilanguaging and Gloria Anzaldúa’s fluid epistemological practices embedded in linguistic choices are deeply associated with the notion of translanguaging. This concept, defined by Ofélia Garcia and Li Wei as a linguistic phenomenon in which all an individual’s linguistic repertoire is used to conceive meaning, is an important element in shaping the main character’s subjectivity and a tool of resistance regarding processes of cultural assimilation and linguistic oppression. Therefore, it is regarded as a product of semiotic processes of meaning-making, and thus dependable on intersections experienced by bilingual subjects. In this sense, translanguaging is a vital element to the maintenance of cultural subjectivities by promoting hybrid bilingual subjectivities. The article is organized in a bibliographic review, followed by an analysis on how the concepts mentioned before are represented in the novel.